Oncocytic Lipoadenoma: A Rare Case of Parotid Gland Tumor and Review of the Literature - Chen-lin Chi; Tseng-tong Kuo; Li-yu Lee (Korean Society of Pathologists & the Korean Society for Cytopathology, 2015)
Oncocytic lipoadenoma is a rare tumor, with only 18 cases having been reported since the first in 1998. We encountered a case of oncocytic lipoadenoma presenting as a slowly growing parotid mass in a 71-year-old man. This tumor is characteristically comprised of a mixture of oncocytes and adipocytes. The present case is one of five reported cases of oncocytic lipoadenoma showing sebaceous differentiation. The results of immunohistochemical study with DOG1 antibody supported the origination of this tumor in the striated duct.